Dilema Generasi Z: Antara Patriotisme dan Godaan Produk Asing - Rizki, Hafidh; Sasongko, Rolan Mart; Saraswati, Yudhistira; Balqis, Fadhila (SMARTINDO, 2024)
This abstract presents findings on the dilemma faced by Generation Z in Indonesia, who are torn between maintaining patriotism and loyalty to local products, and the strong allure of foreign products promoted through social media. This study aims to examine the extent to which the phenomenon of